Anomalous Carrier Transport in Ambipolar Field‐Effect Transistor of Large Diameter Single‐Walled Carbon Nanotube Network. (30th November 2015) - Bisri, Satria Zulkarnaen; Derenskyi, Vladimir; Gomulya, Widianta; Salazar‐Rios, Jorge Mario; Fritsch, Martin; Fröhlich, Nils; Jung, Stefan; Allard, Sybille; Scherf, Ullrich; Loi, Maria Antonietta
Abstract : A demonstration of ambipolar transistors of polymer‐wrapped single‐walled carbon nanotubes (SWNTs) provides an opportunity to scrutinize transport mechanism of electrons and holes in this system. Anomalous temperature‐dependent nonlinear transport behavior is observed in large diameter SWNTs. This suggests an interplay between the intrinsic transport of individual tubes and the percolative network properties, highlighting the nature of polymer‐wrapped SWNTs as a complex hybrid material.